Chamadas por Deus: características do pastorado feminino na cidade de Fortaleza - Silva, Eliana Coelho da (2014)
The present research seeks to analyze the narratives of the trajectories of Protestant Christian women up to their admission to the pastoral office, focusing on the meaning of women’s ordination as given by the female ministers. In this paper, some existing cases in Fortaleza were presented, and the characteristics of a female pastoral care and the models found in this field were noted. The models in the field are found in the equation of “permanence and rupture” variables as related to the biblical model of women which permeates the religious mindset of the female ministers. A qualitative methodology was used with life narratives for the purpose of analyzing their life trajectories, understanding what the process is like in the rise of women to the pastoral office in different denominational settings.